Critical Success Factors of Motivation Factors, Entrepreneurial Competencies, and Entrepreneurial Success in Homestay Program in Sabah, Malaysia - Kelvin Yong; Brahim Chekima; Tam Yin Ling @Adeline Tam; Chang Mui Ling @Dyana Chang; Rudy Ansar; Suddin Lada; Rafidah Nordin (Penerbit Akademia Baru, 2024)
The study aimed to identify and evaluate the critical success factors (CSFs) of motivation factors and entrepreneurial competencies that affect entrepreneurial success in the Sabah homestay program. Data were collected from a sample of 181 homestay entrepreneurs in Sabah using a survey questionnaire. The resource-based view was used to conceptualize the study. The study of entrepreneurial success in homestay entrepreneurs is rarely reported in the existing literature. In fact, there is limited consensus on the selection of a proper set of measurements for assessing entrepreneurial success in entrepreneurship studies. This study is to fills the gap by adding more literature on entrepreneurial success in the context of the homestay industry. The reliability analysis showed that the survey is a reliable measure of the five constructs related to entrepreneurial success. The constructs with the highest reliability are entrepreneurial success and motivation factors-pull. The construct with the lowest reliability is motivation factors-push. The findings contribute to our understanding of the relationship between motivation factors, entrepreneurial competencies, and entrepreneurial success in the context of homestay entrepreneurs in Sabah. The findings are also useful for the Ministry of Tourism, Arts and Culture (MOTAC) strategy goals 2021-2025 and solving sustainable development goals. Future research should investigate the structural relationship between motivation factors, entrepreneurial competencies, and entrepreneurial success in the Sabah homestay program.